PARENT’S PERSPECTIVE ON EDUCATIONAL GAMES: PHENOMENOGRAPHY STUDY IN INDONESIA - Pramuditya, Surya Amami; Wahyudin; Nurlaelah, Elah (International Journal of Psychosocial Rehabilitation, 2020)
The development of games in Indonesia is quite popular, making games a part of modern people’s lives for children and adults. Pros and cons also occur regarding the impact of playing games (commercial games). Games that contain elements of violence can have a negative impact on users. However, there is also a positive impact of playing games, which can improve the cognitive and spatial abilities of a child. Mathematical educational game (in the application), is a game in which there are educational and learning elements, inserted mathematics learning content in the form of questions and material. This study aims to describe parents’ perspective on educational games that contain mathematics learning content as instructional media. This research will focus on parents of educators and not educators. The research design uses phenomenography, where researchers want to see parents’ perspective on the phenomenon of educational games as instructional media. From the results of this study, obtained a positive perspective of the educational game with some suggest. Keeping in mind the age, playing time and supervision of children, most parents agree that educational games can be an instructional media for their children.